2007
DOI: 10.1029/2007gl030516
|View full text |Cite
|
Sign up to set email alerts
|

Polar mesosphere summer echoes at Wasa, Antarctica (73°S): First observations and comparison with 68°N

Abstract: [1] Polar mesosphere summer echoes (PMSE)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 20 publications
3
51
0
Order By: Relevance
“…The MARA radar is described in Kirkwood et al (2007). The Davis radar is described in Morris et al (2006) and Latteck et al (2007).…”
Section: Observational Techniquementioning
confidence: 99%
See 3 more Smart Citations
“…The MARA radar is described in Kirkwood et al (2007). The Davis radar is described in Morris et al (2006) and Latteck et al (2007).…”
Section: Observational Techniquementioning
confidence: 99%
“…The threshold was chosen so as to be well above the background noise at Wasa, see Kirkwood et al (2007) for details. The more powerful Davis radar can detect weaker PMSE than this, this is one reason why it is important to compare volume reflectivity and occurrence above a specified volume reflectivity threshold when comparing data from different radars.…”
Section: Day-to-day Variation Of Pmse Strength and Occurrencementioning
confidence: 99%
See 2 more Smart Citations
“…The current understanding of this phenomenon has been summarized by Rapp and Lübken (2004). PMSE have been observed at different stations, among others at Andenes (69 • N, 16 • E) (Bremer et al, 2003), at Tromsoe (69 • N, 19 • E) (Röttger et al, 1988), at Kiruna (68 • N, 21 • E) , at Svalbard (78 • N, 16 • E) (Hall and Röttger, 2001), and also in the Southern Hemisphere at Davis (69 • S, 78 • E) (Morris et al, 2004, at Halley (76 • S, 27 • W) (Jarvis et al, 2005), and at Wasa (73 • S, 13 • W) (Kirkwood et al, 2007). Latteck et al (2007) have found that PMSE in the Southern Hemisphere occur with a smaller reflectivity than those in the Northern Hemisphere.…”
mentioning
confidence: 99%